Review on Free Space Optics - Thakur, Er. Rajeev; Singh, Er. Sukhbir; Sharma, Er. Abhishek (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Present era demands high bandwidth with high data rates especially for internet. For high data rates requires high speed transmission medium like optical fiber. To overcome the bottle neck of last mile communication free space optics has emerged as a better option for radio engineers. Using Infrared beams provides license free spectrum, high bandwidth with maximum data rates. In this paper different aspects for utilizing an FSO link are reviewed showing there advantages and disadvantages. Â